2018
DOI: 10.1007/s10874-018-9378-z
|View full text |Cite
|
Sign up to set email alerts
|

Size-resolved characteristics of inorganic ionic species in atmospheric aerosols at a regional background site on the South African Highveld

Abstract: Aerosols consist of organic and inorganic species, and the composition and concentration of these species depends on their sources, chemical transformation and sinks. In this study an assessment of major inorganic ions determined in three aerosol particle size ranges collected for one year at Welgegund in South Africa was conducted. SO4 2and ammonium (NH4 +) dominated the PM1 size fraction, while SO4 2and nitrate (NO3) dominated the PM1-2.5 and PM2.5-10 size fractions. SO4 2had the highest contribution in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…The species K + , an excellent tracer for wood and biomass burning (Zhang et al, 2013;Yu et al, 2016), is present in higher abundances during winter, as also observed by Venter et al (2018) at Welgegund. This is consistent with the fire burning season, which reaches maximum intensity in South Africa in September (Scholes et al, 1996a and b).…”
Section: Ionic Sosupporting
confidence: 63%
See 1 more Smart Citation
“…The species K + , an excellent tracer for wood and biomass burning (Zhang et al, 2013;Yu et al, 2016), is present in higher abundances during winter, as also observed by Venter et al (2018) at Welgegund. This is consistent with the fire burning season, which reaches maximum intensity in South Africa in September (Scholes et al, 1996a and b).…”
Section: Ionic Sosupporting
confidence: 63%
“…2and NH 4 + were the most abundant species in PM 2.5 . This has also been seen in a number of studies undertaken at various sites in South Africa (Tiitta et al, 2014;Conradie et al, 2016;Venter et al, 2018;Muyemeki et al, 2021). These species are strongly correlated at both sites, again indicating a common secondary origin, such as coal combustion, of these species.…”
Section: Ionic Somentioning
confidence: 52%
“…This can possibly be attributed to the occurrence of potassium chloride (KCl) in the fresh smoke of burning savannah grass, which can react to form halogenated organic compounds (Aurela et al 2016). Venter et al (2018) collected inorganic aerosols at Welgegund from…”
Section: Fire Countsmentioning
confidence: 99%
“…In addition, the winter months are also characterised by increased household combustion for space heating and cooking, while seasonal open biomass burning generally occurs in the period from August to October, typically peaking during spring in September (Laban et al, 2018). Furthermore, the removal rate of atmospheric pollutants associated with precipitation is also reduced during the dry season (Venter et al, 2018).…”
Section: Site Descriptionsmentioning
confidence: 99%